Can LDL cholesterol be too low? Possible risks of extremely low levels. (June 2017) - Olsson, A. G.; Angelin, B.; Assmann, G.; Binder, C. J.; Björkhem, I.; Cedazo‐Minguez, A.; Cohen, J.; von Eckardstein, A.; Farinaro, E.; Müller‐Wieland, D.; Parhofer, K. G.; Parini, P.; et al.
Abstract: Following the continuous accumulation of evidence supporting the beneficial role of reducing low‐density lipoprotein cholesterol (LDL‐C) levels in the treatment and prevention of atherosclerotic cardiovascular disease and its complications, therapeutic possibilities now exist to lower LDL‐C to very low levels, similar to or even lower than those seen in newborns and nonhuman species. In addition to the important task of evaluating potential side effects of such treatments, the question arises whether extremely low LDL‐C levels per se may provoke adverse effects in humans. In this review, we summarize information from studies of human cellular and organ physiology, phenotypic characterization of rare genetic diseases of lipid metabolism, and experience from clinical trials. Specifically, we emphasize the importance of the robustness of the regulatory systems that maintain balanced fluxes and levels of cholesterol at both cellular and organismal levels. Even at extremely low LDL‐C levels, critical capacities of steroid hormone and bile acid production are preserved, and the presence of a cholesterol blood–brain barrier protects cells in the central nervous system. Apparent relationships sometimes reported between less pronounced low LDL‐C levels and disease states such as cancer, depression, infectious disease and others can generally be explained as secondary phenomena. Drug‐related side effects including an increased propensity for development of type 2 diabetes occur during statin treatment, whilst further evaluation of more potent LDL‐lowering treatments such as PCSK9 inhibitors is needed. Experience from the recently reported and ongoing large event‐driven trials are of great interest, and further evaluation including careful analysis of cognitive functions will be important. Abstract : This is an article from the symposium: Risks and benefits of Extremely Low LDL Cholesterol.